Fast sparse recovery and coherence factor weighting in optoacoustic tomography - He, Hailong; Prakash, Jaya; Buehler, Andreas; Ntziachristos, Vasilis (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
Sparse recovery algorithms have shown great potential to reconstruct images with limited view datasets in optoacoustic tomography, with a disadvantage of being computational expensive. In this paper, we improve the fast convergent Split Augmented Lagrangian Shrinkage Algorithm (SALSA) method based on least square QR (LSQR) formulation for performing accelerated reconstructions. Further, coherence factor is calculated to weight the final reconstruction result, which can further reduce artifacts arising in limited-view scenarios and acoustically heterogeneous mediums. Several phantom and biological experiments indicate that the accelerated SALSA method with coherence factor (ASALSA-CF) can provide improved reconstructions and much faster convergence compared to existing sparse recovery methods.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Image quality enhancement; Model-based reconstruction; Optoacoustic tomography; Sparse recovery method